ECOLOGICAL DOMINANCE AND ENVIRONMENTAL HEALTH IMPLICATIONS OF INVASIVE PTERYGOPLICHTHYS PARDALIS IN DKI JAKARTA - Rita Ramayulis; Rosidi Roslan (Lux Mensana: Journal of Scientific Health, 2026)
Introduction. Suckermouth catfish (Pterygoplichthys pardalis) is among the most prominent invasive exotic fish species in Indonesian urban waters, with its dominance in DKI Jakarta Province particularly evident along the Ciliwung River system subjected to sustained anthropogenic pressure. Method. This study employed a systematic narrative review of peer-reviewed journal articles, institutional reports, undergraduate theses, and official government documents, with sources selected against explicit inclusion criteria covering relevance, methodological clarity, and policy value. Result & Analysis. The dominance of suckermouth catfish in Jakarta is sustained by tolerance for degraded water quality, high reproductive fecundity, and dietary flexibility. A fish reinventory of the Ciliwung River between 2023 and 2024 identified the species among the five most abundant of 37 recorded, confirming that invasive dominance persists despite overall improvements in species richness. Microplastic particles were detected in the gills and digestive tract of specimens from South Jakarta, and ectoparasites were recorded in fish from the same urban habitat, indicating a layered environmental health risk associated with utilisation of the species as a food source. Discussion. Suckermouth catfish functions simultaneously as an invasive species and as an ecological indicator of urban river degradation. Effective control requires an integrated ecosystem-based approach prioritising water quality improvement, adaptive harvesting, habitat restoration, and cross-sectoral governance.